2009
DOI: 10.1371/journal.pgen.1000726
|View full text |Cite
|
Sign up to set email alerts
|

The Schizosaccharomyces pombe JmjC-Protein, Msc1, Prevents H2A.Z Localization in Centromeric and Subtelomeric Chromatin Domains

Abstract: Eukaryotic genomes are repetitively packaged into chromatin by nucleosomes, however they are regulated by the differences between nucleosomes, which establish various chromatin states. Local chromatin cues direct the inheritance and propagation of chromatin status via self-reinforcing epigenetic mechanisms. Replication-independent histone exchange could potentially perturb chromatin status if histone exchange chaperones, such as Swr1C, loaded histone variants into wrong sites. Here we show that in Schizosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 84 publications
7
92
1
Order By: Relevance
“…Bdf1 is also part of the Swr1 complex that is required for the deposition of histone variant H2A.Z (Krogan et al 2003;Kobor et al 2004;Mizuguchi et al 2004), which is also involved in counteracting heterochromatin spreading (Meneghini et al 2003). There is a Bdf1 homolog in fission yeast, which is part of the fission yeast Swr1 complex (Buchanan et al 2009;Hou et al 2010). However, fission yeast Bdf1 is not involved in boundary function at IRCs (Supplemental Fig.…”
Section: The Role Of Bdf2 In Boundary Formationmentioning
confidence: 99%
“…Bdf1 is also part of the Swr1 complex that is required for the deposition of histone variant H2A.Z (Krogan et al 2003;Kobor et al 2004;Mizuguchi et al 2004), which is also involved in counteracting heterochromatin spreading (Meneghini et al 2003). There is a Bdf1 homolog in fission yeast, which is part of the fission yeast Swr1 complex (Buchanan et al 2009;Hou et al 2010). However, fission yeast Bdf1 is not involved in boundary function at IRCs (Supplemental Fig.…”
Section: The Role Of Bdf2 In Boundary Formationmentioning
confidence: 99%
“…Work in the fission yeast S. pombe revealed that the loss of H2A.Z results in silencing defects at centromeres, as well as defective chromosome segregation. 55,56 Interestingly, these phenotypes were observed despite no changes in centromeric levels of CENP-A. It remains to be determined, however,…”
mentioning
confidence: 95%
“…Further suggesting a role for Msc1 in chromatin biology, Msc1 has been found consistently as a component of the fission yeast Swr1C complex (Buchanan et al 2009;Kim et al 2009;Zofall et al 2009;Hou et al 2010;Qiu et al 2010), which facilitates the exchange of histone H2A.Z for H2A at specific chromosomal locations. Cells lacking Msc1 exhibit elevated levels of histone H3 dimethyl-K9 at pericentromeric heterochromatin, consistent with persistence of the fission yeast HP1 homolog Swi6 in this region (Lawrence and Volpe 2009).…”
Section: Discussionmentioning
confidence: 98%
“…As is true for human KDM5A (Nishibuchi et al 2014), Msc1 associates with HDAC activity (Ahmed et al 2004), although there is no evidence to date indicating that Msc1 exists in a stable physical complex with purified fission yeast HDACs Clr6, Clr3, and Sir2 (Nicolas et al 2007;Sugiyama et al 2007;Buchanan et al 2009;Wang et al 2013;Zilio et al 2014). Further suggesting a role for Msc1 in chromatin biology, Msc1 has been found consistently as a component of the fission yeast Swr1C complex (Buchanan et al 2009;Kim et al 2009;Zofall et al 2009;Hou et al 2010;Qiu et al 2010), which facilitates the exchange of histone H2A.Z for H2A at specific chromosomal locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation